Art Without boundaries - Anderson, Jack 1935- (University of Iowa, 1997)
Dance critic Anderson offers a sweeping panorama of modern dance that comes across with the same dynamism and urgency of purpose as the subject itself. Starting with Isadora Duncan's seminal steps toward becoming the free spirit of modernism, Anderson offers an excellent, condensed survey of a phenomenon that started at the beginning of this century. Breaking away from the constraints of ballet, each autonomous development found its own idiosyncratic way, creating myriad styles, theories, techniques and aliases which are now grouped under the cloak of modern dance. To be sure, there were many names--Sound Dance, Expression Dance, New Dance--and some choreographers even came to be reconciled with ballet, such as Kurt Jooss and Carolyn Carlson. Anderson has a remarkable talent for engaging the reader in the complexities of the vibrant dramatis personae of the dance scene. These sketches of American, European and Asian performers are fascinating, as is the depiction of their social and cultural milieux. While necessarily limited in depth, Anderson's impressionistic account deserves credit for its scope, which includes many lesser-known and now forgotten performers. Marking the most original aspects and signal events of this art form's evolution, this is welcome as a concise reference work on the modern dance movement.